Coliform Removal in Membrane Bioreactor and Disinfection during Hospital Wastewater Treatment - Chart Chiemchaisri; Wilai Chiemchaisri; Sujipat Dachsrijan; Chitsuphang Saengam (Journal of Engineering and Technological Sciences, 2022)
This study investigated coliform removal from hospital wastewater in a membrane bioreactor (MBR) and disinfection using either chlorine or ozone. A laboratory-scale MBR equipped with a hollow-fiber membrane module was operated with hydraulic retention times varied at 3 and 6 hours. The disinfection of MBR effluent was carried out using either chlorine or ozone with concentrations varied between 1 and 10 mg/l and contact time varied between 1 and 30 min. During 150 days of MBR operation, organic removal efficiencies averaged 96.5% and 97.7% for BOD and 73.6% and 84.1% during its operation at an HRT of 3 and 6 hours respectively. Simultaneously, 6.7 and 6.4 log reduction of total coliforms and 6.2 and 6.1 log reduction of E. coli were achieved under these respective HRT conditions. The use of chlorine for disinfection of MBR effluent could eliminate total coliforms and E. coli completely at >6 and 3 mg/L at 30 min contact time, whereas only >3 and 1 mg/L was required for ozone at the same contact time. There was a significant improvement of disinfection efficacy of solid-free MBR effluent compared to that of activated sludge effluent.